Analisis Pengaruh Modal Bank, Ukuran Bank, Konsentrasi Pasar, Kepemilikan, Inflasi Terhadap Profitabilitas Bank - Serly, Serly; Jennifer, Jennifer (Universitas Pendidikan Ganesha, 2021)
The purpose of this study is to determine the effect of bank capital, bank size, concentration, ownership, inflation on bank profitability. The method that is used by this study is panel data regression analysis method and this study uses secondary data and the data needed by researchers is obtained from the reports of public companies engaged in banking in Indonesia and listed on the IDX (Indonesian Stock Exchange) during the 2016-2020 period. The results of the study stated that bank capital had no significant effect on bank profitability, bank size had a positive and significant effect on bank profitability, market concentration had no significant effect on bank profitability, ownership had no significant effect on bank profitability, and inflation had a positive and significant effect on bank profitability.Keywords: Bank Profitability, Internal Characteristic, Industry Structure, Economy Situation